Vídeo educativo e entrevista motivacional para promoção da autoeficácia materna na prevenção da diarreia infantil: abordagem individual - Nascimento, Ludmila Alves (2018)
This study aimed to evaluate the intervention with the educational video and the motivational interview for the prevention of self-help in the prevention of childhood diarrhea. This is an experimental study, of the Clinical Trial type, Randomized with a comparative group (video-educative and brief motivational interview). The course was carried out in two Units of Primary Health Care, in Fortaleza / CE. The measure was made by 121 mothers of children under 5 years. Three instruments were applied: the form with socio-demographic, health and child health data; a Self-efficacy Scale for Childhood Diarrhea Prevention; and, by telephone, the reduced form for investigation of diarrhea. The first data collection occurred in the period from June to October of 2015, in three moments: the first one, regarding the health unit, through the application of the form, before the educational intervention. In the 2nd and 3rd moments, a scale and the diarrhea investigation form were applied by telephone, one month and two months after the first stage, respectively. A comparison force was analyzed by CR and 95% CI and the comparisons were made through the X2, likelihood ratio, Student and Mann-Whitney tests. The study was approved by the Committee of Ethics in Research of the Federal University of Ceará under opinion 1,116,855. The intervention and comparison groups were homogeneous at the baseline. The participation of mothers in educational intervention is the risk factor for the occurrence of childhood diarrhea, since the children of women with moderate self-efficacy are more likely to be affected by diarrhea than high self-efficacy. Women with moderate self-efficacy were 8.5 times more likely to be affected by diarrhea. A parental in children with high practice in children should not be a major. It was concluded, therefore, that the program was effective in promoting self-esteem in the prevention of childhood diarrhea and the occurrence of childhood diarrhea in the youngest children whose mothers participated in the educational intervention.